Developing and evaluating a computerized adaptive testing version of the Word Part Levels Test. (January 2019) - Mizumoto, Atsushi; Sasao, Yosuke; Webb, Stuart A.
The knowledge about affix plays a vital role in the development of word knowledge and vocabulary acquisition. A test for diagnostic information on the level of affix knowledge would be useful in order to inform the test users of what learners have gained or lacked in this integral component of vocabulary knowledge. This paper reports the development and evaluation of a computerized adaptive testing (CAT) version of the Word Part Levels Test (WPLT), created by Sasao and Webb (2017). The CAT-WPLT was developed to maximize further the effectiveness of the WPLT as a diagnostic test. It was administered to 760 Japanese university EFL (English as a foreign language) learners. The evaluation was based on the comparison of measurement accuracy with the fixed-item version of the WPLT. The results show that the CAT-WPLT can provide test users with diagnostic information on test-taker's strengths and weaknesses in affix knowledge with smaller number of items and with the same or greater precision than the previous versions of the WPLT. Pedagogical implications for using the CAT-WPLT are discussed along with issues in utilizing computer adaptivity.